Modeling the Impact of Fabrication Variabilities on the Performance of Silicon Avalanche Photodetectors - David Liu; Luca F. Errico; Matteo G. C. Alasio; Mike Zhu; Enrico Bellotti (IEEE Photonics Journal)
This work presents a systematic study of the sensitivities of silicon avalanche photodiode (APD) performance metrics, including gain, excess noise, and bandwidth, to potential variabilities in the fabrication process. The APDs simulations are performed using a state-of-the-art Full-Band Monte Carlo (FBMC) device simulator with the integrated band structure and scattering rates calculated $\mathit{ab{-}initio}$ with density-functional theory (DFT). The focus of this work is placed on the performance of CMOS-compatible lateral transport separate-absorber-multiplier APDs (SAM APDs) fabricated on an SOI layer. The FBMC material models are validated against experimental data for carrier velocities and impact ionization coefficients, in addition to the reported APD performance of a germanium-on-silicon (Ge-on-Si) separate-absorber-charge-multiplier APD (SACM APD). The fabrication variations considered for the SAM APD include slight variations to the doping concentration and physical dimensions of the multiplier and absorber regions, as well as the thickness of the SOI layer. The results show that fabrication variations may have significant effects on the gain of the APD, but minimally affect the excess noise factor and bandwidth of the devices.